Integrating YouTube into EAP Pedagogy to Foster Students’ Academic Speaking Competence in EFL Classrooms - Ida Maulida (STAI Hubbulwathan Duri, 2026)
The increasing demand for English for Academic Purposes (EAP) proficiency requires EFL learners to develop advanced academic speaking skills. However, limited exposure to authentic academic discourse remains a major challenge. Digital platforms such as YouTube may provide multimodal input to support speaking development.This study examines whether integrating YouTube into EAP pedagogy improves students’ academic speaking competence. A quasi-experimental pre-test–post-test non-equivalent control group design was used with N = 14 university EFL students (n = 7 per group) over 8 sessions (one semester). Data were collected through CEFR-based speaking tests, audio/video recordings, and rater scores, with an additional Likert-scale questionnaire for the experimental group. Quantitative data were analyzed using paired- and independent-samples t-tests, and N-gain scores; qualitative support came from learner perception data.Both groups improved significantly; however, the experimental group showed larger gains (M_pre = 61.14, SD = 2.41; M_post = 81.57, SD = 2.64) than the control group (M_pre = 61.00, SD = 2.16; M_post = 68.57, SD = 1.72). Paired t-tests indicated significant improvement in the experimental group, t(6) = −55.38, p .001, with a large effect. N-gain scores were moderate for the experimental group (52.75%) and low for the control group (19.41%). Questionnaire results indicated positive perceptions (M ≈ 4.43–4.71).Findings suggest that YouTube integration may enhance academic speaking through authentic input and multimodal learning. Pedagogically, structured video-based tasks are recommended in EAP instruction. However, results should be interpreted cautiously due to the small sample size and non-random assignment.